Prevalence of hypertension and its determinant factors among workers at port container terminal - Mohamad Daud, Nurul Izzati; Mohd Elias, Saliza (Universiti Putra Malaysia Press, 2023)
Introduction: Port container terminal workers have high potential to develop hypertension due to their work nature that exposed to high altitude working area, long working hours and other risk factors. Most workers at port container terminals were male who are at higher risk to get hypertension according to National Health and Morbidity Survey 2019. It is important for the port workers to maintain a healthy lifestyle for them to improve their quality of work as well as to avoid from getting chronic diseases like hypertension. Objective: This cross-sectional study was aimed to determine the most significant risks factors associated with hypertension among the port workers. Methods: A total of 200 male port container terminal workers participated in this study. Sociodemographic background, lifestyle, and work-related factors were obtained by using questionnaire which consists of 5 sections; A: Socio Demographic Information; B: Working Characteristics; C: Disease History; D; Sample Measurement; and E: Daily Dietary Intake. The blood pressure of the workers was obtained by using Omron HEM-7221-Z Automatic Blood Pressure Monitor. Results: The prevalence of hypertension among the workers was 50.5%. The most significant risk factors associated with hypertension were education level (OR=2.4, 95% CI: 1.14, 4.88) and BMI (OR=2.7, 95% CI: 1.09, 6.67). Conclusion: The high prevalence of hypertension among the workers were contributed by low level of education and unhealthy BMI. Thus, intervention programs are needed to be initiated by the company to educate the workers along with regular health monitoring to counter this problem from getting more serious.